Utilização do metabissulfito de potássio no processo de fermentação etanólica para controle de leveduras e bactérias contaminantes - Paraluppi, Anna Lívia (Universidade Federal de São Carlos, 2017)
One of the main concerns in the ethanol-producing industries is the growth control of undesirable microorganisms that can cause decrease in the fermentative yield. Among non-Saccharomyces yeasts which can contaminate the fermentation process, the genus Dekkera is the most important because it is able to grow in fermentation conditions and be adapted to the substrates. Regarding the bacteria, Lactobacillus is the most representative genus. In the wine industry, several antimicrobial agents are utilized to control the undesirable yeast and bacteria populations, among them the sulphur dioxide (SO2) which is used in the form of sulphite salts. However, the microbial control by this substance is not known yet in the sugar and alcohol industries, in which the acid treatment of the cells and antibiotics are largely utilized to control the growth of bacteria. In this context, this work aimed to verify the effect of the addition of potassium metabisulphite (PMB) in two steps of the fermentative process for fuel alcohol production: to the raw sugarcane juice and to the acid treatment of the cells. In the first step, PMB concentration and exposure time to the antimicrobial were determined to cause decrease in the number of native yeast and bacteria in the sugarcane juice. Secondly, the minimum inhibitory concentration of PMB was determined to control the growth of Dekkera bruxellensis, an important yeast contaminant of the alcoholic fermentation, when added to the acid treatment of the cells, both in pure culture and in co-culture with Saccharomyces cerevisiae and Lactobacillus fermentum. The effect of this treatment on the fermentative parameters was also analysed. The PMB was effective to control the growth of native yeast and bacteria in the sugarcane juice at the concentration of 800 mg/L with exposure time that varied from 3 to 6 hours, resulting in a maximal reduction of one log cycle for yeasts and from 1.5 to 1.9 log cycles for bacteria. When added to the acid treatment of the cells (pH 2.0), a reduction of approximately one log cycle of D. bruxellensis was verified from the concentration of 225 mg/L of PMB. However, in co-culture with S. cerevisiae and L. fermentum, this concentration also resulted in the decrease of S. cerevisiae cell number, with negative effect on ethanol production. In a cell-recycled batch fermentation, the combination of acid treatment and 150 mg/L of PMB caused a substantial decrease in S. cerevisiae viability as well in the growth of both contaminants, with reduction in the ethanol production and fermentative efficiency. Although the potassium metabisulphite is effective in the context of wine fermentation, it was not appropriate to the fuel ethanol production especially due to the peculiar characteristics of the substrate and the conditions in which the fermentation is carried out.
Utilization of potassium metabisulphite in the ethanolic fermentation process to control the growth of contaminant yeast and bacteria
Keywords: Dióxido de enxofre; Caldo de cana; Tratamento ácido; Fermentação; Etanol; Sulfur dioxide; Sugarcane juice; Acid treatment; Fermentation; Ethanol; CIENCIAS AGRARIAS